ANALISIS BENTUK-BENTUK PLURALISME DAN ANALISIS DASAR KEANEKARAMAGAN KULTURAL - Rohimin Rohimin; A. Suradi; Aan Supian; Rupiah Rupiah (Al-Idaroh: Media Pemikiran Manajemen Dakwah, 2024)
This study explains the analysis of forms of pluralism and the basic analysis of cultural diversity in Indonesia. Indonesia is known as a pluralistic nation, which marks the nature of this plurality is the existence of cultural diversity that can be seen from the differences in language, national sku, and religious beliefs. In this study, the researcher will discuss the meaning of pluralism, the important pillars of pluralism, and forms of pluralism.